The influence of different physical exercise amounts on learning burnout in adolescents: The mediating effect of self-efficacy - Fu, Wensheng; Li, Yan; Liu, Yajun; Li, Dan; Wang, Gang; Liu, Yongsen; Zhang, Tingran; Zheng, Yunfeng (Frontiers in Psychology, 2023)
Objective To explore the effect of physical exercise on learning burnout in adolescents, and to reveal the mediating effect of self-efficacy between different physical exercise amounts and learning burnout. Methods A total of 610 adolescents from 5 primary and middle schools in Chongqing, China were investigated with the Physical Exercise Rating Scale (PARS-3), the General Self-Efficacy Scale (GSES), and the Learning Burnout Scale (LBS). The SPSS21.0 and AMOS21.0 statistical software were used to process and analyze the data. Results (1) The physical exercise amount in boys was significantly higher than that in girls, but there was no significant gender difference in self-efficacy and learning burnout. Meanwhile, the academic alienation and low sense of achievement of primary school students were significantly lower than that of junior high school students, and there was no significant difference in the physical exercise amount and self-efficacy. (2) The physical exercise amount in adolescents was positively correlated with self-efficacy (r = 0.41), negatively correlated with learning burnout (r = −0.46), and self-efficacy was negatively correlated with learning burnout (r = −0.45). (3) The physical exercise amount could directly and negatively predict the learning burnout of adolescents (β = −0.40), and self-efficacy played a partial mediating effect between the amount of physical exercise and learning burnout (ES = -0.19). (4) Self-efficacy had no significant mediating effect between low exercise amount and learning burnout, but had a significant partial mediating effect between moderate (ES = -0.15) and high exercise amount (ES = -0.22) and learning burnout, and the partial mediating effect between high exercise amount and learning burnout was the highest. Conclusion Physical exercise was an effective way to prevent or reduce learning burnout in adolescents. It can not only directly affect learning burnout, but also indirectly affect learning burnout through the mediating effect of self-efficacy. It should be pointed out that maintaining a sufficient amount of physical exercise is crucial to improving self-efficacy and reducing learning burnout.